Development and characterization of an innovative synbiotic fermented beverage based on vegetable soybean - Battistini, Carolina (2018)
Soymilk was produced from vegetable soybean and fermented by probiotics (Lactobacillusacidophilus La-5, Bifidobacterium animalis Bb-12) in co-culture with Streptococcus thermophilus.The composition of the fermented beverage and oligosaccharides content were determined. The effect of fructooligosaccharides and inulin on the fermentation time and viability of pro-biotic microorganisms throughout 28 days of storage at 5◦C were evaluated. The soymilkfrom vegetable soybeans was fermented in just 3.2 h, when pH reached 4.8. Fermentationreduced the contents of stachyose and raffinose in soymilk. Prebiotics had no effect on acidi-fication rate and on viability of B. animalis and S. thermophilus in the fermented beverage. Theviable counts of B. animalis Bb-12 remained above 108CFU mL−1in the fermented soymilkduring 28 days of storage at 5◦C while L. acidophilus La-5 was decreased by 1 log CFU mL−1.The fermented soymilk from vegetable soybeans showed to be a good food matrix to deliverprobiotic bacteria, as well as a soy product with a lower content of non-digestible oligosac-charides.